2020
DOI: 10.21203/rs.3.rs-28242/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High expression of Fibroblast activation protein (FAP) predicts poor outcome in high-grade serous ovarian cancer

Abstract: Abstract Background: High-grade serous ovarian cancer (HSOC) is a fatal form of ovarian cancer. Previous studies indicated some potential biomarkers for clinical evaluation of HSOC prognosis. However, there is a lack of systematic analysis of different expression genes (DEGs) to screen and detect significant biomarkers of HSOC. Method and materials: TCGA database was conducted to analyze relevant genes expression in HSOC. Ou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…LAMA5 has been shown to be expressed in endometrioid ovarian cancer [41] and ovarian clear cell carcinoma [42], but to our knowledge has not be described in HGSOC. Decreased COL2A1 expression [43] and elevated COL16A1 expression [44, 45] have been correlated to poor prognosis in HGSOC. Finally, one study demonstrated a decrease in tropoelastin expression in ovarian tumors relative to normal ovarian tissue [46].…”
Section: Discussionmentioning
confidence: 99%
“…LAMA5 has been shown to be expressed in endometrioid ovarian cancer [41] and ovarian clear cell carcinoma [42], but to our knowledge has not be described in HGSOC. Decreased COL2A1 expression [43] and elevated COL16A1 expression [44, 45] have been correlated to poor prognosis in HGSOC. Finally, one study demonstrated a decrease in tropoelastin expression in ovarian tumors relative to normal ovarian tissue [46].…”
Section: Discussionmentioning
confidence: 99%